Trends in adult medical wards admissions of Botshabelo District Hospital 2006-2008 - Chaka, Adeline Pulane (My University, 2011)
BACKGROUND: Trends on medical admissions provide important information to health services planners and implementers. Knowledge of the changing patterns of disease profiles and causes of hospitalisation will help to understand the burden of diseases and address emerging disease patterns and health care needs of a given population. The prevalence of HIV/AIDS and changing patterns of diseases like chronic diseases and infections like tuberculosis (TB) as causes of morbidity and mortality need to be researched, in order to bring about changes in their management and the management of health services. Seeing that there is little or no information on causes of admissions in Botshabelo District Hospital, there was an assumption that HIV/AIDS is the leading cause of medical admissions. The study described the demographic profile, disease profile and their outcomes for patients admitted in the medical wards of Botshabelo District Hospital over a three year period. It will also determine the causes of mortality and the average length of stay by disease profile. AIM: To describe admission trends among adult medical patients in Botshabelo District Hospital. METHODOLOGY: A descriptive, cross-sectional study design was used for this study. The setting of this study was the Botshabelo District Hospital in the Motheo Health District in the Free State Province, using both the male and female adult wards of the hospital. A retrospective record review of patients admitted during 2006-2008 was done. Information was collected from the Admission and Discharge Registers and patients records, using a datasheet. Data on the following variables was collected: patient profiles, admission rates, mortality profiles, outcomes and average length of stay. The collected, validated data was analysed using the Epi- Info 8 software. RESULTS: Seven hundred and three patients were sampled over the three year period of 2006-2008 at Botshabelo District Hospital. There was a slight increase in the number of admissions from 2402 in 2006 to 2498 in 2008. The mean age of admissions was 45.3 years. The average length of stay was 5 days, with a range of 1-9 days. Tuberculosis and HIV were the leading diagnoses, while cerebrovascular diseases, congestive cardiac failure (CCF), hypertension and diabetes were in the top ten causes of admissions as well. Deaths significantly increased over the three years from 38.8% of admissions in 2006 to 54.7% of admissions in 2008. It was found that there was a greater odds dying in female patients (OR 1.55) and older patients (18.79 in the oldest age group), patients with HIV (OR 4.93) and blood disorders (OR 5.97) as compared to circulatory disorders but there was a lower odds of 0.36 in patients residing in H-section. This could be due to the fact that the H-section community is mostly a working and younger community whereas the A-section community is comprised of an older and poorer community of people who came from the farms. CONCLUSION: The research provided reasons for admissions, and mortality in the medical wards. Indeed HIV/AIDS and TB are major public health problems. According to this study mortality caused by HIV/AIDS composed 21.1% and TB 12.6%. In the top ten diseases that caused admissions, HIV in 2006 was 33.6% and was number one cause of admission. In 2007 and 2008 TB was number one at 26%and 23% respectively. There appears to be a serious problem with the increasing mortality in patients admitted in the wards. The information and the recommendations made from the research will assist the health planners at various levels like the district, provincial and national level, in restructuring or improving health services and redistributing resources. Improvement around HIV/AIDS and tuberculosis management needs to be prioritised.